Empire, migration and identity in the British world - Fedorowich, Kent, 1959-; Thompson, Andrew S. (Andrew Stuart), 1968- (Manchester : Manchester University Press, 2013)
This volume brings together established scholars with a new generation of migration and transnational historians. Their work weaves together the'new' imperial and the'new' migration histories, and explores the interplay of migration within and between the local, regional, imperial, and transnational arenas.
Introduction : mapping the contours of the British world : empire, migration and identity / Kent Fedorowich and Andrew S. Thompson -- Malthus and the uses of British emigration / Eric Richards --'Sprung from ourselves' : British interpretations of mid-nineteenth-century racial demographics / Kathrin Levitan -- Religious nationalism and clerical emigrants to Australia, 1828-1900 / Hilary M. Carey -- Resistance and accommodation in Christian mission : Welsh Presbyterianism in Sylhet, Eastern Bengal, 1860-1940 / Aled Jones -- Asian migration and the British world, c. 1850-1914 / Rachel Bright -- Righting the record? British child migration : the case of the Middlemore Homes, 1872-1972 / Michele Langfield -- Travelling colonist : British emigration and the construction of Anglo-Canadian privilege / Lisa Chilton --'Dear Grace...Love Madie' : interpreting a migrant's letters from Australia, 1926-27 / Stephen Constantine -- Staying on or going'home'? Settlers' decisions upon Zambian independence / Jo Duffy --'I'm a citizen of the world' : late twentieth-century British emigration and global identities - the end of the'British world'? / A. James Hammerton -- Multiculturalism, decolonization and immigration : integration policy in Britain and France after the second world war / Eleanor Passmore and Andrew S. Thompson.
Includes bibliographical references and index.
Keywords: Group identity -- United Kingdom; British -- Foreign countries -- History; National characteristics, British; Great Britain -- Emigration and immigration -- History; Great Britain -- Colonies -- History